2018
DOI: 10.1088/1361-6439/aac66c
|View full text |Cite
|
Sign up to set email alerts
|

Optical biosensing in microfluidics using nanoporous microbeads and amorphous silicon thin-film photodiodes: quantitative analysis of molecular recognition and signal transduction

Abstract: Microfluidic devices with integrated optical-to-electrical signal transduction using miniaturized photodetectors can address the need for compact and portable biosensing platforms for medical, veterinary, environmental and food safety applications. However, for different applications the features of the microfluidic point-of-need device will differ in order to be fit-for-purpose, namely the minimum detectable limits, the target sensitivity, and the detection time. Therefore, in order to perform an adequate opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The colorimetric signal is directly (sandwich) or inversely (competitive) proportional to the concentration of target protein in the sample. In this agarose bead-based setup, this colorimetric signal was previously observed to be at least 10-fold more sensitive than organic fluorophores coupled with fluorescence measurements, due to the possibility of accumulating signal over time. After developing the signal, the device is discarded since regeneration protocols to efficiently remove the captured antigens and wash the colored precipitates may hinder the performance of the biotinylated anti-IgG and anti-CHO HCP antibodies.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The colorimetric signal is directly (sandwich) or inversely (competitive) proportional to the concentration of target protein in the sample. In this agarose bead-based setup, this colorimetric signal was previously observed to be at least 10-fold more sensitive than organic fluorophores coupled with fluorescence measurements, due to the possibility of accumulating signal over time. After developing the signal, the device is discarded since regeneration protocols to efficiently remove the captured antigens and wash the colored precipitates may hinder the performance of the biotinylated anti-IgG and anti-CHO HCP antibodies.…”
Section: Resultsmentioning
confidence: 97%
“…The continuous flow of solution minimizes mass-transport limitations along the column and reduces time to achieve equilibrium conditions. 25 , 26 After flowing the sample, a colorimetric signal is generated using a TMB-blotting substrate solution, continuously flowed through the device. The enzymatic reaction with TMB results in the formation of blue precipitates that continuously accumulate on the beads and are not washed away by the liquid flow, contrarily to soluble TMB substrate typically used in ELISAs, which would be suboptimal in this case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microcolumn design comprises two channel heights to facilitate the physical entrapment of the agarose beads [72]. To obtain these devices, polydimethylsiloxane (PDMS) was employed by replicating a two-level SU-8 master, as previously described elsewhere [73]. Briefly, these include the fabrication of two aluminum masks by direct-write optical lithography (DWL) and wet etching of aluminum.…”
Section: Microfluidic Microcolumn Fabricationmentioning
confidence: 99%
“…Regeneration not only allows performing more assays on a single chip, but also enables the measurement of a control sample under the same experimental conditions. Our group has previously demonstrated that using agarose nanoporous microbeads inside microchannels enhances the sensitivity of detection of different biomarkers, mostly by increasing the available active surface area and decreasing diffusion times [3,4]. In this work, we report a regenerable microfluidic microbead-based DNA detection system with integrated fluorescence detection.…”
Section: Introductionmentioning
confidence: 95%